2020
DOI: 10.7759/cureus.11599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urinary Incontinence on the Quality of Life of Older Adults in Riyadh: Medical and Sociocultural Perspectives

Abstract: The objective of the study is to determine the impact of urinary incontinence (UI) on the quality of life (QoL) of the Saudi elderly population. Besides, we investigated individuals' help-seeking behaviors and the religious and cultural aspects of UI among the Saudi elderly. Methods We conducted a cross-sectional study using a random sample of 150 Saudi older adults of both genders. The participants were outpatient clinics of government and private hospitals in Riyadh from January-March 2019. Volunteer medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
5
19
0
1
Order By: Relevance
“…Secondly, the public’s misconceptions about PFD stigmatised women with this disease because of poor social awareness. The stigma reduces the possibility of women disclosing their illness and seeking help [ 24 ]. Thirdly, owing to the overarching influence of traditional Chinese concepts, some women in rural areas have a low degree of self-identity and largely rely on their husbands when it comes to making decisions about major family affairs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the public’s misconceptions about PFD stigmatised women with this disease because of poor social awareness. The stigma reduces the possibility of women disclosing their illness and seeking help [ 24 ]. Thirdly, owing to the overarching influence of traditional Chinese concepts, some women in rural areas have a low degree of self-identity and largely rely on their husbands when it comes to making decisions about major family affairs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the public's misconceptions on PFD stigmatized the women with this disease because of poor social awareness. The stigma reduces the possibility of women disclosing their illness and seeking help [27]. Third, owing to the overarching in uence of traditional Chinese concepts, some women in rural areas have a low degree of self-identity and largely rely on their husbands when it comes to making decisions about major family affairs [28].…”
Section: Discussionmentioning
confidence: 99%
“…How the older adults cope with this disease, and attitudes about this disease are very important in the older adults and the society in which the older adults live ( Avery et al, 2013 ) and can affect their psychosocial health as well as their quality of life ( Alshammari et al, 2020 ). Evidence has demonstrated that older women handle these hurdles depending on their social and cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, each disease is caused, experienced, and managed differently by different people based on the social and cultural backgrounds of the society they live in van den Muijsenbergh and Lagro-Janssen (2006) , Andersson et al (2008) , Hayder and Schnepp (2010) , Gjerde (2012) , Shirazi et al (2014) , Özkan et al (2015) , Heidari et al (2021) , Shakery et al (2021) . Thus, to determine the psychosocial effects of urinary incontinence on older women, their sociocultural backgrounds should be considered ( Sinclair and Ramsay, 2011 ; Laganà et al, 2014 ; Alshammari et al, 2020 ). On the other hand, regarding each society’s sociocultural backgrounds, identifying the experiences of older women suffering from urinary incontinence, finding the strategies they use for the management of the disease, and determining the effects of those strategies on various health dimensions, particularly psychosocial health, can help nurses and other healthcare team members identify and evaluate this problem amongst older women and take measures to provide these patients with training and healthcare services.…”
Section: Introductionmentioning
confidence: 99%